Internet czy świat realny. Gdzie według użytkowników Sieci naprawdę toczy się życie? - Anna Kęsicka, Anna Kęsicka (Człowiek i Społeczeństwo, 2015)
The article compares the relations between people on the Internet and the real world. It presents a historical outline of the development of these relations on the Internet with a special focus on the analysis of the demographic profile of the Internet users at the beginning of the Internet and in 2014. The article is based on a body of research that was carried out by both subjects monitoring the Internet market and the author. While discussing the development of the Internet, the author uses the diffusion of information theory developed by Everett Rogers and refers to earlier theories explaining relations on the Internet.